IMPLEMENTASI AKUNTANSI PENGELOLAAN DANA ZAKAT, DAN INFAK/SEDEKAH BERDASARKAN PSAK NO. 109 PADA UNIT PENGUMPUL ZAKAT (UPZ) MASJID IMAM BONJOL - Indriyani Susanti, - (2019)
This studiy is a qualitative research that aims to determine the implementation of accounting management of zakat funds, dan infaq/Shadaqoh based on PSAK No.109 on The Unit Pengumpul Zakat (UPZ) Masjid Imam Bonjol. This research is a treatment of recognition and measurement, presentation, management of zakat fundsand infaq / charity in accordance with generally accepted standards. The generallyaccepted standard intended in this study is "Statement of Financial Accounting Standards (PSAK) No. 109", with data collection techniques used are interviews and supporting documents such as financial data originating from UPZ. The results ofthis study indicate that the UPZ Masjid Imam Bonjol has not fully implemented in accordance with PSAK 109. As for those who are not yet suitable, such as the presentation of financial statements presented by UPZ Masjid Imam Bonjol.